2018
DOI: 10.3390/molecules23102593
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling of Fruit Powders of Twenty Sorbus L. Cultivars

Abstract: Rowanberries have been traditionally used in various processed foods. Scientific research demonstrates the pharmacological effects of Sorbus L. fruits are determined by their unique composition of biologically active compounds. The aim of this study was to determine the composition of flavonoids, phenolic acids, anthocyanins, carotenoids, organic acids and sugars as well as the total antioxidant activity in fruit powders of 20 Sorbus cultivars. Chemical profiles of rowanberry fruit powders vary significantly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 42 publications
2
42
2
Order By: Relevance
“…It is evident that among phytochemicals and other nutrients, polyphenolic compounds and ascorbic acid may be considered as the most valuable health beneficial constituents, which have been reported in various anatomical parts of Sorbus spp. The polyphenolics, which may influence the colour and flavour, have demonstrated antioxidant [54,81], antidiabetic [11,82] anti-hyperlipidemic [83], anti-inflammatory [84], antimicrobial [85], anticancer [86,87] antiviral [67], antifungal [79], antitumoral [88], anti-periodontal [89], and anti-osteoarthritis [90] effects, as well as vasoprotective [84], neuroprotective [26,91,92], cardioprotective [36], hepatoprotective [7], properties and COX-2 (cyclooxygenase-2) inhibitory [93] activities. Many of these activities are correlated to antioxidant capacity of bioactive compounds, which at cellular level may neutralize excessive reactive oxygen species, and thereby protect important biomolecules in the conditions of oxidative stress, which can cause cellular injury and development of chronic diseases.…”
Section: Promising Health Benefits and Related Applications In Foodsmentioning
confidence: 99%
“…It is evident that among phytochemicals and other nutrients, polyphenolic compounds and ascorbic acid may be considered as the most valuable health beneficial constituents, which have been reported in various anatomical parts of Sorbus spp. The polyphenolics, which may influence the colour and flavour, have demonstrated antioxidant [54,81], antidiabetic [11,82] anti-hyperlipidemic [83], anti-inflammatory [84], antimicrobial [85], anticancer [86,87] antiviral [67], antifungal [79], antitumoral [88], anti-periodontal [89], and anti-osteoarthritis [90] effects, as well as vasoprotective [84], neuroprotective [26,91,92], cardioprotective [36], hepatoprotective [7], properties and COX-2 (cyclooxygenase-2) inhibitory [93] activities. Many of these activities are correlated to antioxidant capacity of bioactive compounds, which at cellular level may neutralize excessive reactive oxygen species, and thereby protect important biomolecules in the conditions of oxidative stress, which can cause cellular injury and development of chronic diseases.…”
Section: Promising Health Benefits and Related Applications In Foodsmentioning
confidence: 99%
“…Among the close relatives of firethorns are cultivated rowans and service trees (Sorbus sp.). A study on different rowanberry cultivars found from 39 to 2659 mg/kg total carotenoids (23 -1262 mg/kg β-carotene), with variations dependent on cultivar, soil, geographical location [6]. These values are comparable to those found in Pyracantha coccinea M. Roem.…”
Section: Methodsmentioning
confidence: 53%
“…Depending on cultivar and ripening stage, fruits from cultivated rowans and service trees (Sorbus sp.) contain 435 -37000 mg/kg [6,23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the S. commixta fruit also has been used for the treatment of bronchitis and gastrointestinal disorders, as well as for its anti-inflammatory, anti-diabetic, diuretic, and vasorelaxant properties [ 12 , 19 ]. Phytochemical analysis of S. commixta fruits has revealed the presence of active ingredients often used in cosmetics, including rutin, isoquercitrin, caffeoylquinic acid, dicaffeoylquinic acid, neosakuranin, chlorogenic acid, neochlorogenic acid, carotenoids, and ascorbic acid [ 20 , 21 , 22 ], suggesting the potential applicability of S. commixta fruits for the production of herbal cosmetics with anti-melanoma activity. Nonetheless, the anti-melanoma properties of S. commixta fruits are yet to be comprehensively characterized.…”
Section: Introductionmentioning
confidence: 99%